THE EFFECTIVENESS OF VISUAL MATERIALS VERSUS CLASSICAL LITERATURE IN ESL TEACHING (Ustozlar uchun, 2026)
This article investigates the ongoing debate in English as a Second Language (ESL) pedagogy regarding the comparative effectiveness of visual materials — including YouTube videos, films, and multimedia content — versus classical literary texts. The central inquiry examines how literary language deviates from ordinary language and what pedagogical implications this distinction carries.[1] Drawing on historical developments in language teaching methodology, survey data from over one hundred ESL students, and current research in applied linguistics, this study argues that while visual materials offer immediate engagement and communicative fluency, classical literature provides irreplaceable benefits for academic vocabulary acquisition, critical thinking, and cultural literacy. A balanced, integrated approach is recommended for long-term academic success.